Application of anxiolytics and β1-adrenoblockers in combination with cognitive-behavioral therapy to reduce anxiety disorders in young people with vegeto-vascular dystonia - Hrubliak Вячеслав (Psychosomatic Medicine and General Practice, 2021)
The article is devoted to the problem of the influence of autonomic dysfunction and anxiety disorders on the quality of life and performance of young people. The relevance of the study is beyond doubt, because vegetative-vascular dystonia is the most common pathology among adolescents and young adults. The author of the article emphasizes that functional autonomic (vegetative) disorders without appropriate correction eventually transform into organic nosological diseases, such as coronary heart disease and hypertension. Anxiety disorders and panic attacks often accompany vegetative disorders, especially in young people, and are actually obligate in the development of vegetative crises of the cerebral or cardiac type, which as a result leads to temporary disability and reduced quality of life. In the complex treatment of vegetative-vascular dystonia in young people with anxiety disorders, the use of cognitive-behavioral therapy in combination with pharmacotherapy – anxiolytic (buspirone) and a selective β1-adrenergic blocker (bisoprolol) was proposed. The dynamics of the general condition, clinical and physiological indicators and the level of anxiety in persons with cardiac, cephalic and arrhythmic syndromes are determined. As a result of the treatment of young people with vegetative-vascular dystonia, a positive effect of selective β1-adrenergic blockers on the general condition, clinical and cardiodynamic parameters was revealed in the form of disappearance or significant reduction of pain and heart rhythm disorders, normalization of blood pressure, regression of neurotic, especially anxiety disorders with simultaneous cognitive behavioral and anxiolytic therapy with buspirone, which can be recommended for use in young people, as well as young men and adolescents, in the process of training and acquiring professional skills, to improve the quality of life and prevent the development of behavioral disorders and organic complications in the future.